White matter abnormalities of the brain: similar to multiple sclerosis in adolescence (Research, Society and Development, 2021)
Also known as Devic's disease, neuromyelitis optica (NMO) is an autoimmune inflammatory disease that affects the central nervous system, considerably similar to multiple sclerosis (MS). This study aimed to compare the similarities of the clinical feature presented with similar cases found in the medical literature, addressing the symptoms, diagnosis, and treatment. This is a descriptive, retrospective, and qualitative study, done through the technique of direct observation. An adolescent male patient came to our service complaining of weakness in the lower limbs and urinary retention and, subsequently, urinary incontinence, during hospitalization. After undergoing magnetic resonance imaging of the skull, a large lesion with a demyelinating characteristic was evident through the T2 and FLAIR sequences, hyperintense in the white matter of the right cerebral hemisphere, with the exuberant enhancement of the contrasted image. Subsequently, he presented weakness in the left dimidium of the body, with progressive worsening in some days, with the impossibility of walking. The treatment was initiated with pulse therapy of methylprednisolone and interferon beta, obtaining an excellent clinical control of the disease. Thus, diagnostic confirmation was only possible thanks to the identification of a single brain white matter lesion through imaging and serological examination, which constituted a tool of great importance for the differential diagnosis that made it possible to exclude multiple sclerosis and allowed the establishment of timely treatment for neuromyelitis optica.